Master's Programme in Telecommunication Engineering - Vo, Thanh Vinh (My University, 2014)
In today’s market, due to stiff competition, manufacturers must continuously seek for innovation to increase productivity. One potential area of innovation is improving crane operations. Typically, cranes are used in manufacturing or maintenance processes, where productivity and safety are considered as most important requirements. Load swinging during crane’s movement is considered as most severe problem affecting ability to operate crane efficiently .Production queue delay can be greatly reduced if crane sway control is implemented properly. In this paper, the crane load sway phenomenon is modeled and analyzed in depth. As the result, a new solution to suppress load sway is proposed. In contrast with various existing anti-sway solutions, our solution is easy to deploy, fast to converge and independent with load weight as well as crane’s rope length. Moreover, the solution is also very affordable and suitable for most of existing motor drive models .The solution is theoretically verified by simulation with software physics engine. Lastly, several anti-sway hardware prototypes were developed and tested against a real overhead crane in factory. The proposed anti-sway algorithm has been proven to be very effective in minimizing load sway to increase speed and reliability in crane operation.
Keywords: Overhead Crane; Load Sway; Anti-sway; Kalman Filter; Modbus; Inclination Sensor; dsPIC33F; ABB ACS800; Arduino; ASM PTAM27; ADIS16029; ST485; Box2D; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|